Novel Causative RET Mutation in a Japanese Family with Hirschsprung's Disease: Case Report and Factors Impacting Disease Severity - Higuchi, Tsukasa; Yoshizawa, Kazuki; Hatata, Tomoko; Yoshizawa, Katsumi; Takamizawa, Shigeru; Kobayashi, Jun; Kubota, Noriko; Hidaka, Eiko (Journal of Pediatric Genetics, 2020)
RET gene variances confer susceptibility to Hirschsprung's disease (HSCR) with pathogenetic mutations being identified in half of familial cases. This investigation of familial HSCR was aimed to clarify the relationship between genetic mutations and clinical phenotype using next-generation sequencing. A novel c2313C > G(D771E) RET mutation was identified in all three affected family members. The mutation involved the kinase domain, which is believe to impair RET activity and intestinal function. A second RET mutation, c1465G > A(D489N), was found only in the extensive aganglionosis case. We conclude that the novel c2313C > A(D771E) mutation in RET may be pathogenic for HSCR, while the c1465C > G(D489N) mutation may be related to phenotype severity.
Keywords: Hirschsprung's disease; next-generation sequencing; RET